STRATEGI MANAJEMEN PEMASARAN PENDIDIKAN DALAM MENINGKATKAN PENERIMAAN SANTRI BARU DI PONDOK PESANTREN CHAIRUL UMMAM DESA SUBAN - Nurbaiti; Shalahudin; Jamil, Fadlilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic boarding schools (pesantren) are educational institutions that play an important role in providing both religious and general education in Indonesia. In the era of globalization, pesantren face increasing challenges in attracting prospective students, making effective marketing management strategies essential. This study aims to: (1) identify the marketing management strategies implemented at Chairul Umam Islamic Boarding School in Suban Village, (2) analyze the supporting and inhibiting factors in the admission of new students, and (3) evaluate the effectiveness of the marketing strategies applied. This research employed a descriptive qualitative approach. The subjects were selected using purposive sampling. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The validity of the data was ensured through source and technique triangulation. The findings reveal that: (1) marketing strategies were carried out through program planning meetings, student service activities, and promotion using social media and printed media; (2) supporting factors included adequate human resources and institutional cooperation, while inhibiting factors included limited recruitment networks and relatively high operational costs; and (3) evaluation of marketing activities was conducted through foundation meetings and regular monthly meetings to monitor program effectiveness.